Surgical service monitoring and quality control systems at district hospitals in Malawi, Tanzania and Zambia: a mixed-methods study. Issue 12 (16th March 2021) - Clarke, Morgane; Pittalis, Chiara; Borgstein, Eric; Bijlmakers, Leon; Cheelo, Mweene; Ifeanyichi, Martilord; Mwapasa, Gerald; Juma, Adinan; Broekhuizen, Henk; Drury, Grace; Lavy, Chris; Kachimba, John; et al.
Abstract : Background: In low-income and middle-income countries, an estimated one in three clinical adverse events happens in non-complex situations and 83% are preventable. Poor quality of care also leads to inefficient use of human, material and financial resources for health. Improving outcomes and mitigating the risk of adverse events require effective monitoring and quality control systems. Aim: To assess the state of surgical monitoring and quality control systems at district hospitals (DHs) in Malawi, Tanzania and Zambia. Methods: A mixed-methods cross-sectional study of 75 DHs: Malawi (22), Tanzania (30) and Zambia (23). This included a questionnaire, interviews and visual inspection of operating theatre (OT) registers. Data were collected on monitoring and quality systems for surgical activity, processes and outcomes, as well as perceived barriers. Results: 53% (n=40/75) of DHs use more than one OT register to record surgical operations. With the exception of standardised printed OT registers in Zambia, the register format (often handwritten books) and type of data collected varied between DHs. Monthly reports were seldom analysed by surgical teams. Less than 30% of all surveyed DHs used surgical safety checklists (n=22/75), and <15% (n=11/75) performed surgical audits. 73% (n=22/30) of DHs in Tanzania and less than half of DHs in Malawi (n=11/22) and Zambia (n=10/23) conducted surgical case reviews. Reports of surgical morbidity and mortality were compiled in 65% (n=15/23) of Zambian DHs, and in less than one-third of DHs in Tanzania (n=9/30) and Malawi (n=4/22). Reported barriers to monitoring and quality systems included an absence of formalised guidelines, continuous training opportunities as well as inadequate accountability mechanisms. Conclusions: Surgical monitoring and quality control systems were not standard among sampled DHs. Improvements are needed in standardisation of quality measures used; and in ensuring data completeness, analysis and utilisation for improving patient outcomes.